Heromice #10: Sweet Dreams, Sewer Rats! - Stilton, Geronimo (Geronimo Stilton Heromice, 2017)
Great Gouda! Tony Sludge and the Sewer Rats have turned day into night, and they want the sun to stay away forever! Now it's up to the Heromice and the mysterious new crime fighter Super E to stop them. But can Superstilton and his friends bring daylight back to Muskrat City before it's too late?